Gut microbiome and serum short-chain fatty acids are associated with responses to chemo- or targeted therapies in Chinese patients with lung cancer - Chen, Huan-Huan; Wu, Qi-Jun; Zhang, Tie-Ning; Zhao, Yu-Hong (Frontiers in Microbiology, 2023)
Background The association between gut microbes and short-chain fatty acids (SCFAs) and therapeutic responses of patients with lung cancer (LC) receiving therapy remains unknown. Methods Fecal and serum samples were prospectively collected from patients with LC, classified as responders, if they presented durable clinical benefits, and non-responders, if not. The composition of gut microbes was analyzed using 16S ribosomal DNA sequencing. Serum SCFA concentrations were detected using gas chromatography. Cell proliferation, migration, invasion, cell cycle, and apoptosis assays were performed on isobutyric acid-treated A549 cells. Reverse transcription-quantitative PCR, Western blotting, immunocytochemistry, and immunofluorescence staining experiments have been performed to investigate the expression of associated genes or proteins. Results Non-responders harbored higher microbiome α-diversity but lower β-diversity compared with responders. Compared to the patients with low α-diversity, those with high α-diversity showed significantly shorter progression-free survival. Additionally, β-diversity has also been observed between these two groups. Specifically, Parasutterella, Clostridiaceae, and Prevotella_7 were more abundant among responders, whereas Bacteroides_stercoris and Christensenellaceae_R-7_group were more abundant in non-responders. The serum SCFA (especially acetate and isobutyrate) levels tended to be higher in responders. Isobutyric acid inhibited the proliferation, migration, and invasion of A549 cells by inducing apoptosis and G1/S arrest while upregulating the expression of GPR41, GPR43, and GPR5C and downregulating that of PAR1, and increasing the activity of histone acetyltransferases. Conclusion We revealed the influence of gut microbiota and SCFAs on the therapeutic responses in patients with LC and the anti-tumor effect of isobutyric acid, indicating their potential use as therapeutic targets.